The treatment challenges of restless legs syndrome. Issue 9 (September 2016) - Gangadharan, Sanjay; Perkins, Lauren; Sauerbier, Anna; Chaudhuri, K Ray
Abstract : Restless legs syndrome is a common disorder characterised by the uncontrollable urge to move the legs, particularly during inactivity or rest. Although the condition is common and has a high impact on quality of life, diagnosis and appropriate management remain a challenge in the primary care setting.